Immuno‐modification of enhancing stem cells targeting for myocardial repair. Issue 7 (23rd April 2015) - Yu, Jiashing; Wu, Yuan‐Kun; Gu, Yiping; Fang, Qizhi; Sievers, Richard; Ding, Chun‐Hua; Olgin, Jeffrey E; Lee, Randall J
Abstract Despite the controversy in mechanism, rodent and clinical studies have demonstrated beneficial effects of stem/progenitor cell therapy after myocardial infarction (MI). In a rat ischaemic reperfusion MI model, we investigated the effects of immunomodification of CD 34+ cells on heart function and myocardial conduction. Bispecific antibody (BiAb), consisting of an anti‐myosin light chain antibody and anti‐CD45 antibody, injected intravenously was used to direct human CD34+ cells to injured myocardium. Results were compared to echocardiography guided intramyocardial (IM) injection of CD34+ cells and PBS injected intravenously. Treatment was administered 2 days post MI. Echocardiography was performed at 5 weeks and 3 months which demonstrated LV dilatation prevention and fractional shortening improvement in both the BiAb and IM injection approaches, with BiAb achieving better results. Histological analyses demonstrated a decrease in infarct size and increase in arteriogenesis in both BiAb and IM injection. Electrophysiological properties were studied 5 weeks after treatments by optical mapping. Conduction velocity (CV), action potential duration (APD) and rise time were significantly altered in the MI area. The BiAb treated group demonstrated a more normalized activation pattern of conduction and normalization of CV at shorter pacing cycle lengths. The ventricular tachycardia inducibility was lowest in the BiAb treatment group. Intravenous administration of BiAb offers an effective means of stem cell delivery for myocardial repair post‐acute MI. Such non‐invasive approach was shown to offer a distinct advantage to more invasive direct IM delivery.